2015
DOI: 10.1149/2.0191514jes
|View full text |Cite
|
Sign up to set email alerts
|

Review—Advances in Anode and Electrolyte Materials for the Progress of Lithium-Ion and beyond Lithium-Ion Batteries

Abstract: This review attempts to critically discuss the progresses obtained in renewing the chemistry of lithium-ion and beyond lithium-ion batteries. The attention is focused on anode materials, including tin and silicon, graphene and conversion anodes, as well as on electrolytes, comprising polymers, solids, gels and ionic liquids. The paper shows that, although considerable progresses have been achieved in the latest few years, the development of the ideal lithium battery, having high energy density combined with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 52 publications
0
82
0
Order By: Relevance
“…These electrolytes exhibit high Li-ion conductivity and support an adequate solid-electrolyte-interface (SEI) formation, but they present many practical disadvantages, such as being volatile and flammable [1,5,7,8]. One class of electrolytes that are seen as a possible alternative are polymer electrolytes (PE).…”
Section: Introductionmentioning
confidence: 99%
“…These electrolytes exhibit high Li-ion conductivity and support an adequate solid-electrolyte-interface (SEI) formation, but they present many practical disadvantages, such as being volatile and flammable [1,5,7,8]. One class of electrolytes that are seen as a possible alternative are polymer electrolytes (PE).…”
Section: Introductionmentioning
confidence: 99%
“…[1] In this respect, great efforts have been devoted to the optimization of high-capacity anodes [2][3][4][5][6] and high-voltage cathodes, [7][8][9][10] with the aim of remarkably increasing the energy content of the battery.T he energy density of current lithium-ion batteries is considered insufficient to satisfy the challenging requirements of emerging market technologies, such as electric vehicles. [12][13][14][15] Transition-metal oxides( M x O y )m ay react with lithium through conversion to form Li 2 Oa nd metallic M( oxidation state = 0). [12][13][14][15] Transition-metal oxides( M x O y )m ay react with lithium through conversion to form Li 2 Oa nd metallic M( oxidation state = 0).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the energy density of commercial lithium‐ion batteries (LIBs) has increased rapidly, driving the evolution of electric vehicles (EVs) and large‐scale energy storage systems (ESSs). Simultaneously, concerns regarding the safety of LIBs have increasingly been raised due to overheating, fires, and explosions . To resolve these safety issues, much attention has been given to the development of all‐solid‐state batteries (ASBs) as the next‐generation power sources, which are composed of solid instead of liquid electrolytes,.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the energy density of commercial lithiumion batteries (LIBs) has increased rapidly,d riving the evolution of electric vehicles( EVs) and large-scale energy storage systems (ESSs).S imultaneously,c oncerns regarding the safety of LIBs have increasingly been raised due to overheating, fires, and explosions. [1][2][3][4][5][6] To resolve these safety issues, much attention has been given to the development of all-solid-state batteries (ASBs) as the next-generation powers ources, which are composed of solid instead of liquid electrolytes, [7][8][9][10][11][12] .I na ddition to addressing safety concerns, solid electrolytes offer excellent opportunities to further improve the energy and power densities of current LIBs. [13][14][15][16] However,t he development of ASBs has been hindered by the insufficient ionicc onductivity of availables olid electrolytes, which do not meet the standard for successful implementation.R ecently,K anno et al reported Li 10 GeP 2 S 12 (LGPS), as uperionic solide lectrolyte with an ionic conductivity of 12 mS cm À1 ,w hich is comparable to the conductivity of commercial liquid electrolytes.…”
Section: Introductionmentioning
confidence: 99%